Digital control systems implementation and computational techniques - Leondes, Cornelius T. (Control and dynamic systems. Advances in theory and applications, 1996)
Praise for the Series: "This book will be a useful reference to control engineers and researchers. The papers contained cover well the recent advances in the field of modern control theory."--IEEE Group Correspondence "This book will help all those researchers who valiantly try to keep abreast of what is new in the theory and practice of optimal control."--Control